(untitled) (Economic and Political Thought, 2013)
The analysis of non-tariff protectionism presented in the article in the context of its reasons, forms and influence on international trade results in a conclusion that we deal with a phenomenon that has immanently become part of the mechanism of global economy; both in the context of its structural form and opportunistic manifestations of activeness. Rather paradoxically, the countries that have achieved a high level of economic development try to protect their financial status with the use of NTM. Non-tariff protectionism demonstrates its restrictive form especially in the periods of crisis and hits the weaker links of international exchange – less developed countries. The changeable form of contemporary protectionism measures, often defined as a ‘moving target’, makes liberalization activities more difficult. They are more and more complex in the light of changes that are taking place in the contemporary world due to a more and more dynamic scientific and technological progress. That is why TBT/SPS have become so important in the whole range of non-tariff measures and difficulties with curbing their restrictive influence occur. Undoubtedly, it is necessary to increase efforts in order to awaken the conscience about threats resulting from the selfish use of NTM in international exchange and look for effective ways of fighting against non-tariff restrictions. It can be assumed that the efforts on the arena of the WTO and other international organizations that aim at the above-mentioned principles will reach an adequate critical mass necessary to start liberalization activities in international trade in the predictable future.